Utilization of Sensor technology as a Sport Technology Innovation in Athlete Performance Measurement: Research Trends - Muhammad Eka Mardyansyah Simbolon; Dzihan Khilmi Ayu Firdausi; Indra Dwisaputra; Agus Rusdiana; Catur Pebriandani; Renaldo Prayoga (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
The Industrial Revolution 4.0 has led to rapid technological advancements in sports technology, aiming to improve athlete performance and monitor developments. These innovations have had an impact on the sports industry, but have only been felt in developed countries. Existing studies on entrepreneurship, extended reality, e-textiles, and inertial movement units (IMU) have explored various aspects of sports technology. However, no review has focused on sensor technology's use in sports performance. This study bibliometrically evaluates sports technology research from 2008 through 2023, identifying trends in growth, notable publications, top authors, journals, institutions, and nations. The results give readers and researchers new information about the development and growth of sports sensor technology subjects as well as about active and potential research areas. China is the most productive country, contributing 17 publications related to sports technology, while the United Kingdom is the most impactful country with 474 citations.